Papillon-lefèvre syndrome: clinical case of oral rehabilitation with osseointegrated implants - Sousa, Gabriel Augusto Silveira; Sousa Junior, Roberto Lourenço de; Faustino, Isabel Schausltz Pereira; Correia Neto, Ivan José; Lopes, Marcio Ajudarte (Journal of Oral Diagnosis, 2024)
Papillon-Lefèvre syndrome (PLS) is a rare benign, autosomal recessive condition caused by a mutation in the cathepsin C gene. This alteration results in palmar-plantar hyperkeratosis, or thickening of the soles of the feet and palms of the hands, as well as aggressive periodontal disease resulting in the premature loss of deciduous and permanent teeth. The etiology is multifactorial, and is influenced by immunological, genetic or microbial factors. This case report presents a successful prosthetics oral rehabilitation with osseointegrated implants in a 48-year-old female patient with PLS. Although few reports of dental implants in patients with PLS have been published, it seems to be a possible approach in selected patients.